Understanding Consumer Preferences in the Funeral Service Industry: Insights from the Johor Bahru Market - Ahmad, Abd Razak; Chin Khang, Wong; Abu Seman, Noor Aslinda (JBS Nexus, 2025)
Funeral service organisations preserve the memory of the departed as they assist families in mourning. Research examining consumer choices in this market sector is currently relatively sparse. A research investigation explores how ethnic Chinese people in Johor Bahru, Malaysia, prefer their funeral services. A total of 50 respondents participated in this study using Microsoft Forms and quantitative research methods. The convenience sampling method produced data analysed through descriptive techniques in Excel software. All participants belonged to a group that experienced death, yet 70% of this group was directly responsible for organising funerals. A significant 48% of the participants estimated their funeral expenses would fall from RM30,000 to RM34,999. Funeral services were the most popular choice among respondents who wanted services in public funeral facilities (84%) and followed the Buddhist/Taoist religious customs (70%). Research results demonstrate that people need accessible funeral services which also offer transparent pricing and maintain respect for local customs. The providers of funeral services should create inexpensive package solutions which permit flexible payment options. Providing more religious services and better professional support would offer improved solutions for this multicultural community. The support system provided by Johor Bahru funeral providers needs to tackle financial, logistical and cultural considerations to benefit bereaved families effectively.